Dampak Perang Rusia Ukraina terhadap Peningkatan Inflasi Negara-negara Baltik [The Impact of Russia Ukraine War towards the Increase of Inflation in Baltic Countries] - Jhon Maxwell Yosua Pattinussa; Roy Vincentius Pratikno; Rexford David Nugroho (Universitas Pelita Harapan, 2022)
After the COVID-19 economic crisis, the world economy is currently rocked by the Russia-Ukraine war crisis. Inflation and recession occurred in almost all countries. Scarcity of consumer goods occurred throughout Europe and resulted in a prolonged economic crisis over the past year. Some of the most affected countries are Estonia, Lithuania, and Latvia. As a result of these countries' dependence on resources and trade relations with Russia, as well as the European Union's economic policies in recent months, the Baltic countries have fallen into the countries with the highest inflation rates in Europe. Therefore, this journal article aims to understand how and what happened to these Baltic countries. By using a qualitative approach and focusing on providing descriptive-explanative explanations in this journal article, the writing team tries to provide in-depth identification and explanation of the contestation of interests that occurs, and how it impacts the economies of the Baltic countries. Bahasa Indonesia Abstract: Setelah krisis ekonomi COVID-19, saat ini perekonomian dunia diguncangkan dengan krisis perang Rusia-Ukraina. Inflasi dan resesi hampir terjadi di seluruh negara. Kelangkaan barang pakai barang konsumsi terjadi di seluruh wilayah Eropa dan mengakibatkan krisis ekonomi berkepanjangan selama setahun terakhir. Beberapa negara yang paling terkena dampaknya adalah negara Estonia, Lituania, dan Latvia. Akibat dari bergantungnya negara-negara tersebut pada sumber daya dan hubungan dagang dengan Rusia, serta kebijakan ekonomi Uni Eropa dalam beberapa bulan terakhir, negara-negara Baltik terjerumus menjadi negara dengan tingkat inflasi tertinggi di Eropa. Maka dari itu tujuan dari artikel jurnal ini adalah untuk memahami bagaimana dan apa yang terjadi pada negara-negara Baltik ini. Dengan menggunakan pendekatan kualitatif, dan berfokus untuk memberikan penjelasan secara deskriptif-eksplanatif pada jurnal arikel ini, tim tim penulis mencoba untuk memberikan identifikasi dan pemaparan secara mendalam mengenai kontestasi kepentingan yang terjadi, dan bagaimana dampaknya terhadap perekonomian negara-negara Baltik.